Welcome to the desert of the real: resisting a postcolonial reality in the modern Irish novel - Mansouri, Shahriyar (Penerbit Universiti Kebangsaan Malaysia, 2017)
Benedict Anderson claims In Imagined Communities that nationalism and national identity are but fruits of a politicised imagination, and that the nation only acts what the State imagines. A decade later, in Tom Inglis re-examines such an imagination in a postcolonial Irish context, and traces the significance of the land in the process of identity formation. Anderson’s and Inglis’s understanding of personal identity formation resonate with the Deleuzian reading of a Rhizome-based local identity set against a monolithic backdrop of root-tree system. Where the former variety promises an animate, multifaceted identity, the latter conditions the development of Irishness to a closed system in which values are yet to be pronounced by the governing root, namely, the State. This is where one can draw the very red thin line between personal and national perception of reality (of being). The multilayered and dialectical nature of the modern Irish novel and its critical caliber has created an accurate touchstone that enables the Irish to identify the very two sides of reality. For the Irish, on the one hand, reality emerges as a monolithic, obdurate construct, fabricated and observed by the State; and on the other, it materialises as the nation’s memory of economic hardships, political marginalisation, ideological bifurcations, and psychological exiles. By exploring James Joyce’s A Portrait of the Artist as a Young Man (1916) and Flann O’Brien’s The Third Policeman (1974), this paper shall answer the question that Anderson and Inglis failed to address: what made the contemporary Irish literature a difficult reflection of postcolonial identity, which neither accepts the State’s atavistic nativism nor identifies with neocolonial political mindset?